Cargos comissionados da administração pública direta do Rio Grande do Norte: análise comparativa entre o perfil profissional dos cargos comissionados com vínculo funcional e sem vínculo funcional - Portela, Solange Araújo (2014)
The professional profile of public administrators in Brazil is changing very rapidly in recent years, seeking to meet the principle of efficiency by public agencies at all levels. The admission of the permanent government employee under the Public Administration is by competition, however, commissioned positions are free appointment of managers, which allows effective participation of external experts according to their respective standards and norms. In this context, this dissertation seeks to understand the main characteristics of the profile of the occupants of commissioned positions in Direct Public Administration of the State of Rio Grande do Norte, noting the differences between those with functional link with the have nots. For this study, by data collection and content analysis, a mapping of the administrative structure of the Government of the State of Rio Grande do Norte was done, i.e., the organization of the Executive Branch, which is regulated by the Complementary Law no. 163/1999 and its amendments, which consists of 53 (fifty three) entities, these 29 (twenty nine) are agencies of the direct administration and the remaining 24 (twenty four) comprises the indirect administration. With the collected data, analysis on the number of commissioned positions of each organ of the State of Rio Grande do Norte and information on education, age, length of service, gender and functional link with the direct administration was carried out. Data were available from SEARH in June/2013, when they totaled 58,733 (fifty-eight thousand seven hundred thirty-three) servers, these 2.15% (two point fifteen percent) occupy commissioned positions, corresponding to 1,262 commissioned positions under the Direct Administration, below the national average of 4% (four percent). Of total commissioned positions 64.7% (sixty-four point seven percent) have no functional link with the direct administration, while only 35.3% (thirty -five point three percent) have functional link. It was noticed that there are no clear and specific criteria for the appointments of commissioned positions in the State. They occur freely, as provided in the State Constitution. Another conclusion is the importance of Public Administration define and improve their capacity, competence and efficiency in the delivery of public services. For that it is necessary to invest in their workforce composed of permanent employees and commissioned positions to define the appropriate professional profile